The gallery of vanished husbands : a novel - Solomons, Natasha (Plume, 2013)
" A stunning new novel from the New York Times bestselling author of The House at Tyneford London, 1958. It's the eve of the sexual revolution, but in Juliet Montague's conservative Jewish community where only men can divorce women, she finds herself a living widow, invisible. Ever since her husband disappeared seven years ago, Juliet has been a hardworking single mother of two and unnaturally practical. But on her thirtieth birthday, that's all about to change. A wealthy young artist asks to paint her portrait, and Juliet, moved by the powerful desire to be seen, enters into the burgeoning art world of 1960s London, which will bring her fame, fortune, and a life-long love affair"--